Decoding the Future of Digital Health: What AI Wearables Should I Buy for Health Tracking? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Decoding the Future of Digital Health: What AI Wearables Should I Buy for Health Tracking? The landscape of personal health management is undergoing a p...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics